Экология фазана в Черноморском заповеднике - Ардамацкая, Т.Б. (Вестник зоологии, 1970)
В статье говорится о завозе фазанов в Черноморский заповедник г 1962 и 1964 гг. Описываются сроки их гнездования, гнездовые стации и поведение. Приводится перечень поедаемых ими животных и растений. Делается вывод, что условия Черноморского заповедника вполне благоприятны для акклиматизации фазана. In the Black Sea reservation the pheasants were set free twice. For the first time in November , 1962 Phasianus colchicus L. were set free on the Solenoozerny plot and in Volyzhin forest; for the second time in March 1964 — 92 individuals of the Amu Darya form (Phasianus colchicus zarudnyi But. ) wer e released on the Solenoozerny and IvanoRybalchinsky plots. The terms of pheasant nesting, their nest habitats and behaviour in different seasons, composition of vegetabl e and animal feed are discribed. The conclusion is made that food and protection conditions in tw o forest-steppe plots of the Black Sea reservation (Solenoozerny and Ivano-Rybalchinsky) are quite favourable for acclimatization of pheasants.